ЖӘДИД АҒАРТЫЎШЫЛЫҒЫ ҲӘМ ТЕАТР - Сейтмуратов, Қ. (FAN va JAMIYAT, 2017)
The article is devoted to the role of the djaded intelligence of Turkistan in reforming the activities of educational establishments and schools in the creation of national art theatre as a part of the enlightening work.